2021
DOI: 10.14742/ajet.6592
|View full text |Cite
|
Sign up to set email alerts
|

What kind of support do teachers really need in a blended learning context?

Abstract: Teachers in higher education are the principal participants in blended learning (BL). Without their engagement, any attempt at BL might fail. In the process of BL implementation, they are faced with various challenges and are mostly not well prepared. However, studies have often neglected the feeling of teachers and their anxieties during BL implementation. There is insufficient research on teacher-related factors, especially teacher support. To address this question, a questionnaire was conducted among 123 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 31 publications
2
17
0
1
Order By: Relevance
“…In this research, we built a construct to assess teachers' perceived organizational support for blended learning, and the direct path coefficient between them indicated that they are positively related to each other. This finding is in line with implications proposed by Garrison and Kanuka ( 2004 ) and Zhao and Song ( 2021 ), although with more concrete evidence.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In this research, we built a construct to assess teachers' perceived organizational support for blended learning, and the direct path coefficient between them indicated that they are positively related to each other. This finding is in line with implications proposed by Garrison and Kanuka ( 2004 ) and Zhao and Song ( 2021 ), although with more concrete evidence.…”
Section: Discussionsupporting
confidence: 92%
“…Organizational support for blended learning was measured with four items in this research. The items were modified based on Eisenberger et al ( 1986 ) and Eisenberger et al ( 1997 ) for the concept of perceived organizational support and Garrison and Kanuka ( 2004 ) and Zhao and Song ( 2021 ) for organizational issues of blended learning.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hertil er det centralt, hvordan man i så fald fremadrettet bør understøtte digital undervisning. Vi ved fra tidligere forskning, at manglende teknisk kunnen og selvtillid (erfaring) samt manglende organisatorisk understøttelse fungerer som barrierer for underviseres implementering af digitale undervisningsformer (Zhao & Song, 2021). Et andet dansk studie peger ligeledes på, at organisatorisk understøttelse er vigtigt (Lyngdorf et al, 2021).…”
Section: Introduktionunclassified